Effects of exercise on visual evoked potentials - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2005)
The aim of this study was to investigate the effects of acute or habitual exercise on visual evoked potentials (VEP). The study group consisted of 9 female and 7 male volleyball players and the control group contained 9 female and 7 male students who were not involved in any sportive activity. The N75, P100, and N145 latency and amplitudes were measured before and after exercise. Intragroup comparison was made to evaluate the acute effects and intergroup comparison for the chronic effects of exercise. Significant differences were noted between athletes and the sedentary subjects in terms of pre-exercise left-N145 latencies and amplitudes and left -P100 amplitudes. Right-eye N145 latencies of inactive female subjects obtained before and after exercise were also statistically different. The results suggest that acute and habitual exercise affects the VEP responses independent from the body temperature and other physiological parameters. Small sized pre-exercise P100 amplitudes in the athletes can be attributed to the effect of rapid visual-activity-demanding sports on the central nervous system. Visual evoked potentials maybe used as neurophysiological criteria in defining the performance of an athlete.
Keywords: brain; evoked potential; exercise; performance; volleyball; BRAIN; LATENCY; SIZE; AGE; VOLLEYBALL; MOVEMENTS